Videolaparoscopic colorectal surgery. A new alternative: is it surgical and oncologically valid? - Steinsleger, Ricardo; Harraca, Jorge H; Gallegos, Juan A; Baetti, Mario E (Cirugía del Uruguay, 1994)
A new technique is described far treatment of rectocolonic surgical diseases by means of videolaparoscopy. A prospective study was carried out: 8 patients carriers of benign and malignan/ pathology were included during a 1 O month period. In 3 cases the procedure was converted to conventional surgery and it was completed in the other 5. Feasibility, advantages and disadvantages were analysed as we/1 as the following of standards of oncological surgery in those cases where it was required by the pathology. Jt is concluded that this technique proposed a new approach with no changes in surgical plans. Limitations related to the learning curve and palien/ anatomy appeared.